Recém-nascidos com malformações congênitas: prevalência e cuidados de enfermagem na unidade neonatal - Fontoura, Fabíola Chaves (2012)
The newborns (NB) with congenital malformation (CM) requires from nursing professionals the performance of specific and individualized care. This study aimed at evaluating the prevalence of newborns with congenital malformation in public institutions and the nursing care provided to these children admitted to the Neonatal Unit (NU) in the first 24 hours of life. This is a descriptive, cross-sectional and quantitative study, which was conducted in three Neonatal Units of hospitals (A, B, C) from the city of Fortaleza-CE/Brazil. The sample was composed of 159 newborns; from which 75 belong to institution A; 44 to B; and 40 to C. The data were collected in 2012, from January to June in A and B, and from March to August in C. Records and documents were investigated in the aformentioned units and, subsequently, they were recorded in the proper forms containing maternal and neonatal variables, after approval by the Ethical Committee. Results showed prevalence of 3.3%, 2.1% and 3.6% of malformed newborns in the institutions, respectively. Of the sample, 53% were male, 57% with 37 to 41,6 gestation weeks, 52% weighing between 2,500 g and 3999g, 66% with height 39-49 cm, Apgar score at 1st (60%) and 5th (79%) minutes from seven to ten. Among the implemented therapies to the NB, it should be highlighted oxygenotherapy in Oxy-hood (42%); Zero diet (37%); intravenous hydration (36%); central venous access puncture for infusions (44%); handling for every three hours (89%) and did not undergo surgery throughout the period (75%). Among the dressings, the highlighted location was the sacral region (54%) and the coverage with sterile compress (21%). The diagnosed congenital malformations were categorized according to the classification of the ICD – 10, prevailing those ones belonging to the Musculoskeletal System (30%) and to the Central Nervous System (CNS) (21.1%) highlighting the Congenital clubfoot, Polydactyly, Hydrocephalus and Myelomeningocele. It should also be highlighted the isolated malformations (61%) and the nursing care records involving examinations (24.4%) and oxygenotherapy (16.9%). There were statistically significant associations between the malformations categories and some specific variables: (CM of the CNS) x (GI, Drug Therapy) (CM of the eye, ear, face, neck) x (GI, Drug use and Schooling); (CM of the Circulatory System) x (Maternal age and Drug use) (CM of the Respiratory System) x (Drug use and Drug therapy); (Cleft-lip and palate) x (Maternal age and Drug use); (Others CM of the Digestive System) x (Ventilation modality and Nutrition and Surgery forms); (CM of the Genitalia) x (Gender, Family Income and Nutrition form); (Musculoskeletal CM) x (Number of pregnancies and Ventilation modality); (Others CM) x (GI and weight), and (Chromosomal Abnormalities) x (Maternal age), all with p <0.05. We have concluded that the number of NB with CM it is still prevalent and the nursing staff implements the healthcare according to the clinical conditions, pathology and hemodynamic balance of each NB and not specifically for each type of malformation.